The dual faces of service user participation: Implications for empowerment processes in interprofessional practice. (May 2013) - Kvarnström, Susanne; Hedberg, Berith; Cedersund, Elisabet
Summary : This article reports on an empirical research study exploring and describing variations in how front-line practitioners perceive service user participation (SUP), specifically in interprofessional practice. The settings comprised three Swedish health and social care organizations where the professionals worked in interprofessional teams: a program for chronic pain rehabilitation, a program for surgical treatment of obesity, and a short-term municipal home for older adults. The qualitative study design was informed by a phenomenographic approach and conducted as semi-structured individual interviews with 15 professionals representing nine professions, including social work. Findings : The main findings show seven qualitative variations in understanding of SUP: 1) inclusion in activities and social events, 2) obtaining guidance, 3) having self-determination and choice, 4) getting confirmation from and contact with professionals, 5) negotiating for adjustment, 6) personal responsibility through insight, and 7) circumstance surrounding SUP. Applications : The interprofessional dimensions discerned in the meaning attributed to SUP are mainly described in terms of amplified opportunities for participation. An interesting aspect of the findings is that in all the variations of perceptions of SUP, there are potentials to reverse to their opposites, that is, paradoxes that can be termed 'the dual faces of service user participation'. These aspects stress the need for continuing reflection on practices among both front-line practitioners and managers in empowering and paternalistic processes and on constantly improving organizational and policy conditions to facilitate SUP.